Pesan Dakwah Melalui Film Islami (Studi Tentang Film BILAL: A New Breed Of Hero Analisis Semiotika Charles Sanders Piece) - Retna Dwi Estuningtyas; Erwina Erwina; Ahmad Jauhar Fahruddin (LP2M IAI Muhammadiyah Sinjai, 2022)
The use of film as a medium of da'wah has proven to be effective in conveying the noble values ​​and messages of life. Film is a medium that can be accepted by all groups and the general public. This is in accordance with the mission of Islam to spread love to the whole world. The following research contains an analysis of texts through the media, using the semiotics of Charles Sanders Pierce's model. Semiotics is known as a model of social science that understands the world as a system of relationships with symbols as basic units, namely signs, objects, and interpretations. Semiotics is used here to understand the story of Bilal's journey as a sign with all its problems. The results of this research are expected to be material for further scientific development, especially in communication science which focuses on the use of social media as a medium with various facilities in preaching through films. It is hoped that this research can improve religious knowledge through all media by capturing da'wah messages through religious short films.